Serum Levels of Anti-Citrullinated Protein Antibody (ACPA) and TWEAK in Patients with Rheumatoid Arthritis: Association with Disease Activity and Treatment Modalities - Murat KARKUCAK,; Erhan ÇAPKIN,; Haşim ÇAKIRBAY,; Ayşe AKYÜZ,; Ahmet ALVER,; Ayşegül CANSU,; Duygu DEMİROK,; Mehmet TOSUN, (Archives of Rheumatology, 2011)
Objectives: In this study, we evaluated the serum levels of a serum TNF-related weak inducer of apoptosis (TWEAK) and anti-citrullinated protein antibody (ACPA) and investigated the possible correlation of these parameters with disease activity, cytokine levels and anti-TNF-alpha treatment in patients with rheumatoid arthritis (RA). Patients and methods: Fifty-one patients with RA (39 females and 12 males) and 25 healthy controls were enrolled in the study. Of these, 22 patients were on anti-TNF-alpha and 29 were solely on disease-modifying anti-rheumatic drugs. Serum TWEAK, anti-ACPA [anti-modified citrullinated vimentin (MCV) and anticyclic citrullinated peptide, (CCP)], TNF-alpha, and interleukin-1 levels were determined by enzyme-linked immunosorbent assay (ELISA). The disease activity of RA was assessed according to Disease Activity Score 28 (DAS28). Radiographs were scored according to the modified Sharp methods. Results: The RA patients had significantly higher anti-MCV and anti-CCP levels. When RA patients and controls were evaluated for serum TWEAK levels, there was no statistically significant difference (p=0.765). No significant correlation was detected between the anti-CCP, anti-MCV, and modified Sharp scores. A significant positive correlation was determined among anti-MCV, anti-CCP, and modified Sharp scores. There was a negative correlation between anti-CCP levels and serum TWEAK levels in RA patients (r=–0.84, p=0.471) that was not statistically significant. Conclusion: Our study has shown that levels of anti-MCV and anti-CCP are higher in RA patients than in controls, and these also correlates with the modified Sharp scores. TWEAK levels were similar for RA patients receiving different medications and the controls.